L'evolució de les e (breu) i o (breu) + iod en català dins la Romània - Batlle, Mar (Caplletra. Revista Internacional de Filologia, 1996)
This work is a discussed exposition, with references to Romance languages nearer to Catalan, of two hypotesis which have tried to explain peculiar evolution e > [í] and o > [ú] because of the iod in Catalan. The most accepted explanation says the iod was the cause of diphthongation of both vowels (the same as in Occitan) and after this they monophthongized in [í] and [ú] respectivelly, But I try to notice you, by following the line that Badia Margarit in his Gramàtica suggested, also it could be accepted an explanation based on direct inflection of open vowels (the same as in Castilian and Portuguese).